Time and work in eighteenth-century London - Voth, H-J (University of Oxford, 1997)
Witnesses' accounts are used to analyse changes in working hours between 1750 and 1800. Two findings stand out. The paper demonstrates that the information contained in witnesses' accounts allows us to reconstruct historical time-budgets, and provides extensive tests of the new method. It also emerges that the number of annual working hours changed rapidly between the middle and the end of the eighteenth century. Estimates of labour input are presented. These findings have important implications for the issue of total factor productivity during the Industrial Revolution.